STRENGTH CHARACTERIZATION OF DISSIMILAR MATERIAL SAMPLES PRODUCED VIA FUSED FILAMENT FABRICATION (Nonconventional Technologies Review, 2022)
Fused Filament Fabrication is a 3D Printing technology that uses molten thermoplastic material forced through a nozzle to manufacture parts additively. This technology can use many thermoplastic grades and can produce single or multi-material parts depending on printer configuration. However, when printing a component with multiple materials, their compatibility must be considered to ensure proper bonding. The main issue of using non-compatible or low compatible material is that material will not fuse, resulting in poor mechanical properties. This study aimed to investigate if the mechanical properties of standard polymers, Polylactic Acid and Polyethylene Terephthalate can be improved using reinforcing strings of engineering-grades polymers, Polyamide 645 and Polyamide with 20% short carbon fiber reinforcement. The reinforcements were designed as simple strings cores, enveloped by a standard polymer material. The investigation was planned using a Taguchi L8 matrix. The results showed that the mechanical properties and specimens' integrity made of standard polymers could be improved by adding reinforcing strings of engineering-grade polymers.
Keywords: Fused Filament Fabrication; multi-material; composite; low compatibility; reinforcing sting; tensile strength